Displaced center of pressure on the treated side in individuals with essential tremor after radiofrequency ablation: a longitudinal case–control study - Sato, Atsuya; Taira, Takaomi; Kitada, Kazuya; Ando, Toshiki; Hamaguchi, Toyohiro; Konno, Michiko; Kitabatake, Yoshinori; Ishioka, Toshiyuki (Frontiers in Neurology, 2023)
Background Essential tremor (ET) is a common involuntary movement disorder (IMD). Radiofrequency ablation (RFA) targeting the ventral intermediate nucleus (Vim) of the thalamus is a stereotactic neurosurgery performed in individuals with ET when pharmacotherapy is no longer effective. Though the reasons remain largely unclear, certain adverse events are known to appear post-RFA. These may be due to functional changes in the Vim, related to RFA-induced tremor reduction, or an adverse reaction to compensatory movement patterns used to perform movements in the presence of tremor symptoms. Objective This study aimed to understand the characteristics of post-RFA symptoms in individuals with ET. Methods In a longitudinal case–control study, we compared post-RFA symptoms between individuals with ET who underwent Vim-targeted RFA and those with IMD who underwent non-Vim-targeted RFA. Symptoms were compared preoperatively and 1-week and 1-month postoperatively. Quantitative assessments included center-of-pressure (COP) parameters, grip strength, Mini-Mental State Examination, two verbal fluency tests, and three types of physical performance assessments (upper extremity ability, balance ability, and gait ability). Results Individuals with ET after RFA showed horizontal displacements of the COP to the treated side (the dominant side of the RFA target's hemisphere) at 1-week postoperatively compared to the preoperative period. The horizontal COP displacement was associated with balance dysfunction related to postural stability post-RFA. Other COP parameters did not significantly differ between the ET and IMD groups. Conclusion COP displacement to the treated side may be due to a time lag in adjusting postural holding strategies to the long-standing lateral difference in tremor symptoms associated with tremor improvement after RFA.